EFEKTIVITAS PETUNJUK PRAKTIKUM BERBASIS MASALAH DALAM PEMBELAJARAN IPA UNTUK MENDORONG PARTISIPASI AKTIF SISWA - Rahmat, Irwandi (Jurnal Biogenerasi, 2025)
This study aims to analyze the effectiveness of problem-based laboratory guides in enhancing students’ active participation in science learning. The research employed a Posttest-Only Control Group Design involving a sample of 30 students. Data were collected through an observation sheet encompassing four dimensions of active participation: cognitive process, behavioral action, social collaboration, and affective motivation. The results of the Paired Samples t-Test indicated that the Sig. (p) value for all variables was less than 0.05, signifying a significant difference between the control and experimental classes. The overall mean score of students’ active participation increased from 2.01 (moderate category) in the control class to 3.88 (high category) in the experimental class, with the greatest improvement observed in the cognitive dimension. These findings demonstrate that the implementation of problem-based laboratory guides is effective in fostering students’ active engagement, strengthening collaboration, and enhancing learning motivation in science laboratory activities